Human Nature Is the Bride: Bosch’s Nuptial Imaginaries - Cere, Daniel (Religion and the arts, 2020)
Recent scholarship has accented the impact of evolving forms of bridal mysticism on late medieval popular spiritualities of the Low Countries. Under the laicizing impulses of Devotio Moderna, these narratives were extended as models for the spiritual life of the laity as well as the consecrated religious. A number of Bosch’s key works appear to engage and explore the themes of bridal anthropology, as well as advance perspectives on bridal eschatology. These intersections between the Boschian imagination and the evolving tradition of bridal mysticism shed light on the puzzling play of the religious and the erotic in his work.